Analytical considerations and general diagnostic and therapeutic ramifications of milk hormones during lactation. Issue 1 (January 2018) - Wagner, Carol L.; Baatz, John E.; Newton, Danforth; Hollis, Bruce W.
Abstract : In this review, we will discuss the changes that occur in the mammary gland from pregnancy to lactation and the issues surrounding the analysis of circulating and milk hormones during the stages of lactogenesis. There is a cascade of events that must occur to achieve milk synthesis, milk ejection, and successful transfer to the breastfeeding infant. The adequacy and success of this process is no small measure and the assessment of milk production, the hormones involved in this process and the ability to properly diagnose conditions and causes of low milk supply are critical for the health and well-being of the mother-infant breastfeeding dyad. The normative data that have been amassed in past decades suggest that there are certain values or circulating concentrations of milk hormones, that if lacking or low, could explain low milk supply status. Yet, in looking more closely at the tests themselves, the certainly of what constitutes "normal" can vary depending on the preanalytical conditions that the blood or milk sample were obtained, the methods used in obtaining circulating or milk concentrations, and the standardization of how that result is expressed. The standardization of these aspects of breast milk physiology are essential for providing important normative data to health care professionals and researchers and will result in more consistent findings across multi-disciplinary platforms.